Projetos político-pedagógicos em escolas de educação básica: direito à escolarização de estudantes com transtorno do espectro do autismo - Mendes, Maria Fernanda Moreira (2024)
The Politic-Pedagogical Project, democratically constructed, is the document that guides all actions of a school institution, aiming primarily at improving the quality of education and promoting a more participative, responsible, and inclusive educational environment. Due to its inclusive perspective, it should address the needs of all students, including those with Autism Spectrum Disorder. Because students with Autism Spectrum Disorder have very specific characteristics, they require pedagogical adjustments, curricular flexibility, alternative communication, and the presence of a professional to accompany them, depending on their individual needs. Thus, such actions need to be outlined in the Politic-Pedagogical Projects of schools. This dissertation aimed to analyze how legislation regarding the education of students with Autism Spectrum Disorder is present in the Politic-Pedagogical Projects of Basic Education schools at the federal, state, and municipal levels in a large city in the state of Minas Gerais, and to verify if and how it incorporates legislation aimed at these students with ASD. To achieve this objective, we conducted a survey of literature in the field as well as legal documents that assisted us in the discussions of the results. We chose to adopt the critical-social epistemological approach, with Paulo Freire and Dermeval Saviani as the fundamental references that supported our analyses and reflections. The results showed that, in addition to the Politic-Pedagogical Projects of the three schools being outdated, none of them addressed issues related to students with Autism Spectrum Disorder. Given that this population is increasingly entering Basic Education schools, the results indicate the need for these schools to rethink their Politic-Pedagogical Projects and adapt them to the reality that Education, from an inclusive perspective, points us towards.